Ethical Aspects in Knowledge Organization A Discourse Analysis at ISKO International Events - Evangelista, Isadora Victorino [UNESP]; Barros, Thiago Henrique Bragato (Nomos Verlag, 2020)
The present research intended to analyse what is the perception from International Society for Knowledge Organization (ISKO) about Ethical studies in the field. To do that, was applied a discourse analysis in the papers with social contets presented in the international events of the society. Was possible to see a criticism to misrepresentation in languages considered universal, the exclusion of marginalized groups in society, and the change of paradigms of information access from the technological development.